UNETHICAL BEHAVIOR: A MULTIDISCIPLINARY REVIEW OF THE HIGHLY CITED PAPERS - Alina Beattrice VLADU; Diana-Elisabeta MATICA (Annals of the University of Oradea: Economic Science, 2022)
Our multidisciplinary review paper aims to explore the research paradigms of unethical behavior from different academic perspectives. By doing this, our paper contributes to a better understanding of unethical behavior by drawing knowledge from alternative understandings of such behavior. More specifically, our multidisciplinary inquiry aims to summarize the main findings documented by scholars from different disciplines that conducted independent research on the topic using unique perspectives and ideas associated with the field. As such, in order to gain a better understanding of how unethical behavior is examined through a range of different disciplines and areas of research we assessed the highly cited papers found at the intersection of various categories and research areas such as management, business economics, and psychology, ethics, engineering, and environmental sciences and ecology, public environmental occupational health. Having the goal to offer the most representative research on the topic, we based our review on the highly cited papers examining unethical behavior from the Clarivate Analytics’ Web of Science (WoS), the world`s leading scientific citation search and analytical information platform. The results show that the highly cited papers analyzed cluster around two major research themes as antecedents and factors increasing/enabling unethical behavior (e.g. propensity of moral disengagement, psychological entitlement, self-serving justifications, job insecurity, air pollution, polluted social contexts, creativity, favorable attitudes of upper-class toward greed, etc.) and factors deterring or limiting it (e.g. religion, ethical leadership). Given our multidisciplinary review, our study helps provide alternative understandings and important insights on the research of unethical behavior to serve for novel investigations in both practice and theory.